Human Factors Influencing the Implementation of Cobots in High Volume Distribution Centres - Wim Lambrechts; Jessica S. Klaver; Lennart Koudijzer; Janjaap Semeijn (Logistics, 2021)
Order picking is a logistics component of warehouse operations where substantial productivity gains are possible. In this study, we investigate implementation processes of collaborative order picking robots (cobots) and focus on the influence of human factors on their implementation in high volume distribution centres. These human factors are: resistance to change; organisational culture; communication on change; and leadership. Four case companies were selected that have experience with testing and introducing several types of cobot and have successfully implemented (at least) one type of cobot over an extended period. In-depth interviews with operational decision-makers led to the identification of 66 critical incidents related to human factors. The results demonstrate the importance of planning the implementation process in phases. Employees are hesitant or resistant to the change due to a lack of information, experience, and communication. The decisive role of the team leader is crucial to implement cobots successfully, and here the individual character traits (e.g., the variance in commitment, character, and motivation) influence the process as well. Although the introduction of cobots is not yet widespread, and the negative impact on the workforce (i.e., concerning job loss) is currently low, one should be aware of the possible future implications when robotisation becomes structurally embedded. Therefore, this article calls for a stronger link between human factors and the future of work, with a specific focus on reskilling and upskilling of logistics professionals in light of robotisation, rather than binary approaches in which robots are primarily seen as a threat to the current workforce.